RISIKO NPL KREDIT BANK PEMBANGUNAN DAERAH SEBAGAI REGIONAL CHAMPION - Rofikoh Rokhim; Mal Isnaini Sri Mey Yanti (Jurnal Keuangan dan Perbankan, 2014)
The focus of this research was to identify the impact of BPD Regional Champion Program to each bank’s NPL. This research used a panel data analysis for the observation period of 2008 – 2011. The selected random effects model identified the determinant of NPL from bank specific variables and external factors. The Model was then simulated by the indicative targets of minimum loan growth of 20% and minimum portion of productive loan of 40%. This research revealed that the Program might cause higher estimated NPL for 12 banks while for the other 13 banks the estimated NPL would be lower than the real NPL.